Effect of Quercetin and Zinc Oxide Concentrations on pH and In Vitro Activity of Sunscreen Lipstick - Wisudyaningsih, Budipratiwi; Barikah, Kuni Zu'aimah; Kamelia, Ilfi Nur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Quercetin, a naturally occurring flavonoid, exhibits significant antioxidant properties, making it a promising candidate for photoprotective applications. Concurrently, zinc oxide is a well-established physical blocker of ultraviolet A (UV-A) radiation. This study aimed to optimize the synergistic combination of quercetin (as an anti-UV-B agent) and zinc oxide (as an anti-UV-A agent) within a sunscreen lipstick formulation to enhance broad-spectrum photoprotection. A factorial design, implemented using Design Expert 13.0 software, was employed for the optimization. The independent variables were the concentrations of quercetin and zinc oxide, while the dependent responses included pH, Sun Protection Factor (SPF), percentage of Erythema Transmission (%TE), and percentage of Pigmentation Transmission (%TP). Statistical analysis evaluated the individual and interactive effects of the components on these responses. Both quercetin and zinc oxide individually demonstrated a positive influence on increasing the pH and SPF values of the formulations, while concurrently reducing both %TE and %TP values. Notably, a significant synergistic interaction between quercetin and zinc oxide was observed, further influencing the SPF, %TE, and %TP values. The optimized formula, derived from the overlay contour plot generated by the factorial design, comprised 2.5% quercetin and 15% zinc oxide. This optimal combination yielded a pH of 5.027, an SPF of 22.713, a %TE of 0.012, and a %TP of 0.004. The optimized combination of quercetin and zinc oxide in a sunscreen lipstick formulation effectively provided desirable pH values and substantial in vitro sunscreen efficacy. These findings suggest that this novel formulation holds significant potential as a broad-spectrum photoprotective cosmetic product.